Immigrant over- and under-education: The role of home country labour market experience - Matloob Piracha; Massimiliano Tani; Florin Vadean (Institute for the Study of Labor (IZA), 2010)
The cause of immigrant education mismatch in the host country labour market might not necessarily be discrimination or imperfect transferability of human capital, as argued in previous studies. Immigrants who have gained professional experience in the home country in jobs below their education level might be assessed by host country employers as having lower abilities and skills than those expected from their educational qualifications. Using the Longitudinal Survey of Immigrants to Australia we show that a significant part of the variation in the immigrants' probability to be over-/under-educated in the Australian labour market can be explained by having been over-/under-educated in the last job in the home country.
Keywords: C34; J24; J61; 330; immigrants; education-occupation mismatch; sample selection